Coastal upwelling enhances abundance of a symbiotic diazotroph (UCYN-A) and its haptophyte host in the Arctic Ocean - Selden, Corday R.; Einarsson, Sveinn V.; Lowry, Kate E.; Crider, Katherine E.; Pickart, Robert S.; Lin, Peigen; Ashjian, Carin J.; Chappell, P. Dreux (Frontiers in Marine Science, 2022)
The apparently obligate symbiosis between the diazotroph Candidatus Atelocyanobacterium thalassa (UCYN-A) and its haptophyte host, Braarudosphaera bigelowii, has recently been found to fix dinitrogen (N2) in polar waters at rates (per cell) comparable to those observed in the tropical/subtropical oligotrophic ocean basins. This study presents the novel observation that this symbiosis increased in abundance during a wind-driven upwelling event along the Alaskan Beaufort shelfbreak. As upwelling relaxed, the relative abundance of B. bigelowii among eukaryotic phytoplankton increased most significantly in waters over the upper slope. As the host’s nitrogen demands are believed to be supplied primarily by UCYN-A, this response suggests that upwelling may enhance N2 fixation as displaced coastal waters are advected offshore, potentially extending the duration of upwelling-induced phytoplankton blooms. Given that such events are projected to increase in intensity and number with ocean warming, upwelling-driven N2 fixation as a feedback on climate merits investigation.